Ultra-fast YBa2Cu3O7-x direct detectors for the THz frequency range - Thoma, Petra (Karlsruher Schriftenreihe zur Supraleitung / Hrsg. Prof. Dr.-Ing. M. Noe, Prof. Dr. rer. nat. M. Siegel, 2013)
For the analysis and optimization of the picosecond pulsed terahertz radiation generated by electron storage rings or other pulsed sources, ultra-fast detectors are required which are able to resolve picosecond dynamic processes directly in the time domain. In this book, a new direct terahertz detector technology based on the high-temperature superconductor YBa2Cu3O7-x has been developed which opens new routes in the analysis of picosecond time-domain processes with a wide dynamic range.